Therapeutic and pathogenetic animal models for Dolichos pruriens - Coelho, C. de Paula; D'Almeida, V.; Pedrazzolli-Neto, M.; Duran-Filho, C.; Florio, J. C.; Zincaglia, L. M. C.; Bonamin, L. V. (Elsevier B.V., 2006)
The therapeutic and pathogenetic effects of Dolichos pruriens were evaluated using experimental models in rats. In the therapeutic experiment Wistar rats were housed in a heated environment (25 +/- 3 degrees C) to induce itch, and treated with ascending potencies D. pruriens (6 cH, 9 cH, 12 cH and 30 cH), each for 10 days. The positive control group received vehicle (ethanol 30% in water). The negative control group received no treatment and were kept at a standard temperature.In the pathogenetic experiment, all animals were kept at a temperature of 20+/-3 degrees C and treated for 30 consecutive days with D. pruriens 6 or 30 cH, or ethanol vehicle, or no treatment. The experiments were performed blind.The statistical analysis used Bartlett's test, followed by ANOVA/Tuckey-Krammer or Kruskal-Wallis/Dunn. The results point to the existence of therapeutic effects, with inhibition of the itching, skin lesions and fur thinning produced by heat, more evident in later observations, with the 9 12, and 30 cH potencies (Kruskal-Wallis/Dunn; P = 0.001). No changes were observed in the other parameters, such as open field activity and laterality of the itching. In the pathogenetic experiment, no changes were observed in any parameters examined. We conclude that the proposed experimental model demonstrates the therapeutic effect of D. pruriens, but not its pathogenetic effects.
Keywords: homeopathy; Dolichos pruriens; animal model; itch; open field; grooming; pathogenesis